An Overview of Vascular Dysfunction and Determinants: The Case of Children of African Ancestry - Matjuda, Edna N.; Engwa, Godwill Azeh; Sewani-Rusike, Constance R.; Nkeh-Chungag, Benedicta N. (Frontiers in Pediatrics, 2021)
Vascular dysfunction is the hallmark for cardiovascular diseases (CVDs) and it is known to begin early in life, thus, predisposing children and adolescents to risk of CVDs in future. The vascular system is made up of blood vessels such as arteries, veins and capillaries whose function is to maintained by a balance between vasoactive factors including dilatory factors such as nitric oxide, hydrogen sulphide, prostaglandin I2, endothelium derived hyperpolarizing factor, and contracting factors including prostacyclin, endothelin, and thromboxane. The balance between dilatory and constrictive factors is important as it keeps the blood vessels in a homeostaticsis state. However, altered physiological processes as a result of oxidative stress, obesity, hypertension, oxidative stress and other cardiovascular risk factors may lead to vascular damage causing an imbalance of vasoactive factors. Over time, the sustained imbalance of these vasoactive factors may lead to vascular dysfunction which can be assessed by non-invasive methods such as flow mediated dilation, pulse wave velocity, flow mediated slowing, retinal vessel analysis, peripheral vascular reactivity and carotid intima-media thickness assessment. Although there is increasing prevalence of cardiovascular risk factors (obesity and hypertension) in children in sub-Saharan Africa, little is known about how this may affect the vascular function. This review focusses on vasoactive factors of vascular (dys)-function, highlighting on the determinants and consequences of vascular dysfunction. It further describes the non-invasive methods used for vascular (dys)-function assessments and lastly, describes the reports on vascular dysfunction in children of African ancestry.